2021
DOI: 10.1109/access.2021.3051774
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scene Doppler Power Spectrum Modeling of LEO Satellite Channel Based on Atlas Fingerprint Method

Abstract: The modeling of low earth orbit (LEO) satellite channel depends on its Doppler power spectrum. Due to satellite during transit, diversity and dynamic channel scene, the modeling of Doppler power spectrum has two serious problems: one is that the shape of the Doppler power spectrum will vary with the change of scenes and time, but the use of the existing traditional Doppler power spectrum models is difficult to accurately describe them. The other one is that the amount of measured data used for modeling is too … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Every model has advantages and disadvantages, and the selection of a model depends on the needs of the specific application [30,31,32]. Recent research has demonstrated that deep learning models such as CNNs and DBNs outperform more conventional machine learning models such as SVMs and DTs in satellite image classification tasks [33,34,35]. To examine the full potential of ensemble models for the classification of satellite images, additional research is necessary for a variety of scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Every model has advantages and disadvantages, and the selection of a model depends on the needs of the specific application [30,31,32]. Recent research has demonstrated that deep learning models such as CNNs and DBNs outperform more conventional machine learning models such as SVMs and DTs in satellite image classification tasks [33,34,35]. To examine the full potential of ensemble models for the classification of satellite images, additional research is necessary for a variety of scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%